Developing 3D cadastre registration system - Mohd. Hasif Ahmad Nasruddin, author; Muhammad Imzan Hassan, 1976-, author; Alias Abdul Rahman, author; International Symposium and Exhibition on Geoinformation (2007 : Selangor) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL